Fatigue and depression predict reduced health-related quality of life in childhood-onset lupus. (January 2018) - Donnelly, C; Cunningham, N; Jones, J T; Ji, L; Brunner, H I; Kashikar-Zuck, S
We aimed to identify risk factors for persistently reduced health-related quality of life in childhood-onset lupus and describe a risk profile for persistently reduced health-related quality of life. At a tertiary rheumatology clinic, 50 childhood onset lupus patients were assessed twice, approximately six months apart. Measures of disease activity and patient-reported measures of health-related quality of life, pain, depressive symptoms, anxiety and disability were collected at each visit. At visits 1 and 2, respectively, clinically relevant fatigue was present in 66% and 56% of patients; clinically significant depressive symptoms in 26% and 24%; and clinically significant anxiety in 34% and 28%. Poorer health-related quality of life at follow-up was significantly predicted by higher fatigue and depressive symptoms at the initial visit. Using clinically relevant cut-offs for fatigue and depressive symptoms, patients were assigned to Low ( n  = 27) or High Risk ( n  = 23) groups. A profile of significantly greater pain, anxiety and coping difficulties was seen in the High Risk group. Routine assessment of fatigue and mood symptoms in youth with childhood-onset lupus could be helpful in identifying those at risk for persistently poor health-related quality of life. Integration of behavioral interventions to address fatigue and mood symptoms into medical care for such patients may be beneficial, but more research in this area is needed.